Implementation of Fingerprint Absence System and Web-Based Reporting at Roworejo Inposites Center, Negeri Katon Sub District - Widianto Widianto; Mardiyanto Mardiyanto; Sobari Sobari (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2020)
Changes in an institution or performance, one of which is work discipline which is one of the important factors in the quality of service at Roworejo inpatient Puskesmas where attendance is very important and very influential in improving the quality of service to patients and discipline for employees. With the efficient fingerprint attendance system at Roworejo inpatient Puskesmas, employees no longer leave signatures because each individual has something special that only he has. The result of applying fingerprint attendance is more accurate and minimizes attendance manipulation. besides this attendance system is more practical because attendance search is only through ID and is more time-efficient compared to the previous manual attendance where the recapitulation of attendance can be seen according to the desired time span.